Microbial populations, sensory, and volatile compounds profiling of local cooked rice - Mohammad Sabri, Nur-Shahera; Nor Ainy, Mahyudin; Abdullah Sani, Muhamad Shirwan; Han, Ming Gan; Chong, Kah Hui; Padmanabhan, Kousalya; Shan, Jiang; Mahmud Ab Rashid, Nor Khaizura (Oxford University Press, 2023)
Objectives: This study is designed to investigate the microbial populations, sensory, and volatile compounds profling of locally cooked rice stored at room temperature (30 °C) on days 0, 1, 2, and 3 (D0, D1, D2, and D3) for the determination of specifc spoilage organisms (SSOs). Materials and Methods: Microbiological, physicochemical, sensory evaluation, and volatile organic compounds (VOCs) analyses were conducted for samples of cooked rice stored at room temperature on days 0, 1, 2, and 3. SSO of cooked rice was then identifed by linking present organisms with the changes occurring throughout the storage period. Results: Microbiological analysis revealed the presence of spore-forming bacteria, yeast, and moulds, which survived the cooking process. While total viable count exceeded the microbiological limit at 6.90 log CFU/g on D3, panellists deemed cooked rice unacceptable for consumption on D2 at a total sensory score of 11.00, which indicates that D2 was the day cooked rice spoiled. Through culture-dependent and cultureindependent methods, Bacillus cereus was identifed as the sole bacteria observed throughout the storage period, confrming that the bacteria were SSOs. The VOC analysis proposed several metabolites, 3-eicosene, 1-heptadecene, hexacosane, phenol, 4,4ʹ-(1-methylethylidene)bis-, n-nonadecanol-1, and cyclohexanone, as potential spoilage markers of cooked rice. Conclusions: B. cereus is confrmed to be the SSO of cooked rice, in which spoilage occured after 48 h of storage at room temperature. The organoleptic rejection in cooked rice was shown to be linked to the production of various compounds by B. cereus which could be proposed as potential spoilage markers for cooked rice.